THE DEVELOPMENT OF CREATIVITY IN THE STUDENTS OF HIGHER EDUCATION INSTITUTIONS AS AN URGENT PEDAGOGICAL PROBLEM (E Conference Zone, 2022)
In the article in higher education In higher education, the Annotal Teacher's importance is important in the course of today's education, modernization processes, globalization processes for innovative society, training specialists, training, training systems, pedagogical activity, to modernize the efficiency of pedagogical activities. It is shown that the formation of creative specialists is one of the main tasks of the education system of modern society.